Synergistic integration of oxygen doping and a self-imprinted architecture in g-C3N4 for efficient and selective photocatalytic degradation of tetracycline - Xinyang Li; Yangrui Xu; Yipeng Liu; Yu Cheng; Liguang Tang; Hongping Li; Xinlin Liu; Hong Liu; Jie Jin; Ziyang Lu (Journal of Environmental Chemical Engineering, 2026)

Rapid screening method of glucocorticoid residues in sample-limited cell-cultured meat - Peiwen Yu; Simeng Li; Chen Zhang; Xiaohui Li; Hongping Wang; Fen Jin (Food Research International, 2026)

Perfluoroalkyl and polyfluoroalkyl substances exposure and liver disease: A review - Junzheng Peng; Rongbin Gong; Runwei Li; Liang Li; Hongping Yu; Qiuping Wen (Toxicology, 2026)

Machine learning for lithology identification in electrical image logging: A case study of the Chang 73 Sub-Member, Yanchang Formation, East Gansu region, Ordos Basin - Jiaqi Li; Hongping Bao; Shilong Liu; Pingping Shi; Feiming Gao; Liubin Wei; Langlang Wang; Hongyan Yu (Earth Science Informatics, 2026)

Ultrafast and selective removal of Sr2+ by a chain-structured aluminophosphate for nuclear waste remediation - Yucheng Hao; Cheng Hou; Changlin Chen; Mingyang Cao; Shihan Zhang; Xinnan Li; Guangyu Zhang; Fengshan Yu; Hongping Bian (Desalination, 2026)

Optimizing biochar selection for soil amendment: Unraveling the feedstock-texture interplay for enhanced crop performance - Rong Zhang; Zizhen Ma; Linhua Jiang; Wenjie Gao; Hongping He; Heng Yu; Tao Yu; Bo Yang; Chengtun Qu (Bioresource Technology, 2026)

A multiomics analysis of antioxidant and neurotransmitter disorder in honey bees caused by the bioinsecticide, Spinosad - Yinglong Yu; Zhaonan Zhang; Wencai Zhou; Dan Yao; Hongping Zhan; Xingjiang He; Ying Li; Wei Wan; Huajun Li; Xiaoping Wei (Pesticide Biochemistry and Physiology, 2026)

Sex-dependent acute oral toxicity and in vivo distribution of 6:2 chlorinated polyfluorinated ether sulfonate (6:2 Cl-PFESA) in rats - Simeng Li; Peiwen Yu; Bowen Li; Xiaohui Li; Hongping Wang; Fen Jin (Food and Chemical Toxicology, 2026)

Metagenomic Analysis Reveals Alterations in the Gut Microbiome of Preterm Infants with Extrauterine Growth Restriction - Wensi Ni; Huiling Huang; Xin Wang; Aizhen Yu; Jianbing Ren; Hongping Li (Current Microbiology, 2026)

Bioinsecticide matrine causes a cliff-like decline and disorder of gut microbiota, transcriptomics, and metabolomics profiles in honey bees (Apis cerana) - Yinglong Yu; Zhaonan Zhang; Yuanchan Fan; Wencai Zhou; Dan Yao; Hongping Zhan; Xingjiang He; Ying Li; Wei Wan; Xiaoping Wei (Pesticide Biochemistry and Physiology, 2026)

Two new prenyl-substituted natural products from the endophytic fungus Talaromyces sp. XSJC-F4 - Shangfeng Gao; Yiqing Shi; Haidi Li; Hongping Long; Kangping Xu; Xia Yu (Natural Product Research, 2025)

Ba2Y[BO3][Si2O6]:Ce3+ phosphor with high-efficiency blue emission and excellent quantum yield enabled by mixed-dimensional anionic framework engineering - Bohuai Shao; Hongwei Yu; Zhanggui Hu; Jiyang Wang; Yicheng Wu; Hongping Wu (Chemical Engineering Journal, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Co-adsorption of phosphate and rare earth elements (REEs) on goethite induce middle REE-enriched fractionation - Xiaoju Lin; Wenbin Yu; Xiaoliang Liang; Yoshio Takahashi; Jingwen Zhou; Yiping Yang; Meng Chen; Jianxi Zhu; Runliang Zhu; Hongping He (Geochimica et Cosmochimica Acta, 2025)

Residue pattern and risk assessment of validamycin A and spinosyn A in tea using hydrophilic interaction liquid chromatography coupled with tandem mass spectrometry - Aiping Li; Chen Wang; Yunfeng Chai; Zhiming Huang; Binbin Yao; Chengyin Lu; Miao Yu; Hongping Chen (Food Chemistry, 2025)

Orchard variable rate spraying method and experimental study based on multidimensional prescription maps - Chenming Hu; Yu Ru; Shuping Fang; Zifan Rong; Hongping Zhou; Xianghai Yan; Mengnan Liu (Computers and Electronics in Agriculture, 2025)

Distribution, uptake, and daily exposure of per- and polyfluoroalkyl substances in a paddy field: A growth cycle study - Bowen Li; Hongping Wang; Peiwen Yu; Pan Zou; Dongfei Tan; Fen Jin (Journal of Hazardous Materials, 2025)

Dissipation patterns of trisiloxane ethoxylates in cucumber plants and field soils: Insights from different end-capping groups - Simeng Li; Xiaohui Li; Chen Zhang; Bowen Li; Peiwen Yu; Qin Dai; Hongping Wang; Fen Jin (Journal of Hazardous Materials, 2025)

The modifying role of residential greenness on the association between heat waves and adverse birth outcomes: Results from the ELEFANT project - Yuxuan Ma; Yuanyuan Yu; Lei Zhao; Qisijing Liu; Jiayan Ni; Zi Lin; Bin Chen; Weixia Li; Huishu Lin; Yuhong He; Shuhao Shi; Jianqiong Zheng; et al. (Environmental Research, 2025)

Identification of shale lithofacies by well logs based on clustering algorithms - Kun Meng; Shanbin He; Hongping Bao; Xiankun Meng; Taiping Zhao; Binfeng Cao; Xiaorong Luo; Lukman Johnson; Hongyan Yu (Acta Geophysica, 2025)

Lysine 98 in NAC20/NAC26 transcription factors: a key regulator of starch and protein synthesis in rice endosperm - Shanbin Xu; Yu Zhang; Hongping Cai; Yuzhe He; Laibao Chen; Guiping Zhang; Rongbo Chen; Chuanwei Gu; Xuan Teng; Erchao Duan; Ling Jiang; Yulong Ren; et al. (Plant Science, 2024)

Identification of the synonymous variant c.3141G > A in TNRC6B gene that altered RNA splicing by minigene assay - Feiyu Zhou; Hongping Zhong; Bo Wu; Yaqiong Cui; Jiaci Li; Xiaodong Jia; Changshun Yu; Dong Li; Jianbo Shu; Chunquan Cai (Molecular Biology Reports, 2024)

Efficient concentration of viral nucleic acid in wastewater through surfactant releasing and a two-step magnetic bead extraction and purification - Ping He; Wenhao Zhou; Mengwei Jiang; Junping Yu; Hongping Wei (Science of The Total Environment, 2024)

Transcriptome profiling reveals postharvest quality losses of pink Auricularia cornea - Lei Ye; Yu Huang; Bo Zhang; Jianhua Luo; Hongping Liu; Xuezhen Yang; Shijun Ma; Shun Chen; Wengping Zhang; Wei Tan; Xiaolin Li (Postharvest Biology and Technology, 2024)

Simple Equations for Estimating the Large Convergence and the Longitudinal Displacement Profile of a Tunnel - Kai Guan; Wancheng Zhu; Hongping Li; Quanyun Zhang; Qinglei Yu; Xige Liu (Rock Mechanics and Rock Engineering, 2024)

Assessing the future probable maximum precipitation in Utah under global warming - Hongping Gu; Jonathan Meyer; Shih‐Yu Simon Wang; Robert Gillies; Wei Zhang; Everett Taylor (International Journal of Climatology, 2024)
Probable maximum precipitation (PMP) has been an important criterion for designing hydrological infrastructure and it is likely to change with respect to global warming. To assess the potential risk that hydrological infrastructure in the U.S. state of Utah may encounter under the least mitigated emission scenario of Representative Concentration Pathway 8.5 (RCP8.5), this study identified historical (1950–2005) and future (2006–2100) PMP estimates to quantify the range and degree of change for extreme precipitation. The results show that an averaged RCP8.5 simulated 19.2% (3.43°C) increase in dewpoint temperature will result in a 39% (88.39 mm) increase in 24‐h 100‐mi 2 (259 km 2 ) PMP values. It is also found that the rapidly growing metropolitan areas of the state would experience a greater PMP increase (106.43 mm) than that in the state's National Parks and forested areas (93.98 mm). This discovery indicates a vulnerability that could affect both hydrological and metropolitan infrastructure. The planning of the state's infrastructure needs to consider the changing PMP under global warming.

Unveiling the NIMBY effect in construction and demolition waste landfilling: Factors, paths, and solutions - Bo Yu; Jiayuan Wang; Ruipu Li; Qun Wang; Huanyu Wu; Xiaoxiao Xu; Hongping Yuan; Jian Zuo (Journal of Environmental Management, 2024)

Path tracking control for brake-steering tracked vehicles based on an improved pure pursuit algorithm - Chenming Hu; Yu Ru; Xianzhe Li; Shuping Fang; Hongping Zhou; Xianghai Yan; Mengnan Liu; Rong Xie (Biosystems Engineering, 2024)

Experimental transformation of nontronite to kaolinite: implication for ferrallitization of Fe/Mg-rich clays in compositional stratigraphy on Mars - Xiaorong Qin; Jiacheng Liu; Wei Tan; Hongping He; Joseph Michalski; Yu Sun; Shangying Li; Binlong Ye; Yiping Yang; Yiliang Li (Icarus, 2024)

Experiments and CFD simulation of downwash airflow and fog distribution discharged from a single-rotor UAV fitted with a pulse-jet thermal fogging machine - Jian Zhang; Qing Chen; Jian Liu; Yan Wang; Hongping Zhou; Fengbo Yang; Yu Ru (Biosystems Engineering, 2024)

Genetic variants in m5C modification genes are associated with survival of patients with HBV-related hepatocellular carcinoma - Bowen Chen; Moqin Qiu; Rongbin Gong; Yingchun Liu; Zihan Zhou; Qiuping Wen; Xiaoxia Wei; Xiumei Liang; Yanji Jiang; Peiqin Chen; Yuying Wei; Qiongguang Huang; et al. (Archives of Toxicology, 2024)

Design a dual-response two-photon fluorescent probe for simultaneous imaging of mitochondrial viscosity and peroxynitrite in a thrombosis model - Miantai Ye; Xiaohui yu; Yan Yuan; Meng He; Junli zhuang; Sizheng Xiong; Jie Li; Yanying Wang; Chunya Li; Xiaoxing Xiong; Hongping Deng (Analytica Chimica Acta, 2024)

Development of composite amine functionalized polyester microspheres for efficient CO2 capture - Xuewen Chen; Hongping Quan; Jie Yu; Yuling Hu; Zhiyu Huang (Environmental Science and Pollution Research, 2023)

Environmental effects on ammonium adsorption onto clay minerals: Experimental constraints and applications - Amber Jie Yu; Xiaoju Lin; Jianxi Zhu; Hongping He; Long Li (Applied Clay Science, 2023)

Ultra-conductive and transparent epidermal electrodes for simultaneous dual-mode assessment of brain function - Yan Zhao; Yan Zhang; Zhe Liu; Song Zhang; Dekui Song; Yu Zhai; Chunming Lu; Hongping Yan; Nan Liu (Chemical Engineering Journal, 2023)

A multifunctionally reversible detector: Photoacoustic and dual-channel fluorescence sensing for SO2/H2O2 - Yicai Zhu; Junjun Wang; Yingyong Ni; Qingpeng Rao; Xiaojiao Zhu; Jianhua Yu; Sen Wang; Hongping Zhou (Analytica Chimica Acta, 2023)

Genetic variants of SOS2, MAP2K1 and RASGRF2 in the RAS pathway genes predict survival of HBV-related hepatocellular carcinoma patients - Qiuling Lin; Moqin Qiu; Xueyan Wei; Zhouyun xiang; Zihan Zhou; Iiangyan Ji; Xiumei Liang; Xianguo Zhou; Qiuping Wen; Yingchun Liu; Hongping Yu (Archives of Toxicology, 2023)

A luciferase based automated assay for rapid and sensitive detection of SARS-CoV-2 antibodies - Wenhao Zhou; Ping He; Huan Liu; Hongping Wei; Junping Yu (Analytica Chimica Acta, 2023)

Taberdines L and M, two new alkaloids from Tabernaemontana divaricata - Lingling Han; Kepu Huang; Chen Chen; Wentao Zhu; Yehan Ma; Xiaojiang Hao; Hongping He; Yu Zhang (Natural Product Research, 2022)

Optimization of Process Conditions for Ultrasound-Assisted L-Cysteine on Inhibition of Polyphenol Oxidase Activity from Fresh-Cut Potato Using Response Surface Methodology - Erihemu; Yu Jia; Mengru Wang; Xiaoqing Song; Guoqin Li; Meng Zhao; Hongmei Zhu; Hongping Wang (American Journal of Potato Research, 2022)

Assessment of long-term functional maintenance of primary human hepatocytes to predict drug-induced hepatoxicity in vitro - Yi Chen; Dan Tang; Hongping Wu; Yuling Wu; Tianjie Yuan; Hongdan Zhang; Yingfu Jiao; Weifeng Yu; Hexin Yan (Archives of Toxicology, 2021)

Gastrodin alleviates inflammatory injury of cardiomyocytes in septic shock mice via inhibiting NLRP3 expression - Feifei Shao; Lingmin Zhou; Yu Zhang; Hongping Chen; Yu Zhang; Zhihui Guan (In Vitro Cellular & Developmental Biology - Animal, 2021)

Two new monoterpenoid indole alkaloids from Tabernaemontana divaricata - Huansha Yuwen; Yuxi Yuan; Xiaojiang Hao; Hongping He; Yu Zhang (Natural Product Research, 2019)

Electroacupuncture inhibits visceral pain via adenosine receptors in mice with inflammatory bowel disease - Tengfei Hou; Hongchun Xiang; Lingling Yu; Wen Su; Yang Shu; Hongping Li; He Zhu; Lixue Lin; Xuefei Hu; Shangdong Liang; Hong Zhang; Man Li (Purinergic Signalling, 2019)

Reduced neurotrophic factor level is the early event before the functional neuronal deficiency in high-fat diet induced obese mice - Huanhuan Wang; Bing Wang; Hongping Yin; Guoqing Zhang; Liping Yu; Xiangmin Kong; Haiying Yuan; Xingyue Fang; Qibing Liu; Cuiqing Liu; Liyun Shi (Metabolic Brain Disease, 2017)

Comparison between a chimeric lysin ClyH and other enzymes for extracting DNA to detect methicillin resistant Staphylococcus aureus by quantitative PCR - Yuanyuan Hu; Hang Yang; Jing Wang; Yun Zhang; Junping Yu; Hongping Wei (World Journal of Microbiology and Biotechnology, 2016)

Molecular characterization and different expression patterns of the FABP gene family during goat skeletal muscle development - Linjie Wang; Li Li; Jing Jiang; Yan Wang; Tao Zhong; Yu Chen; Yong Wang; Hongping Zhang (Molecular Biology Reports, 2015)

Degradation of methicillin-resistant Staphylococcus aureus biofilms using a chimeric lysin - Hang Yang; Yun Zhang; Yanling Huang; Junping Yu; Hongping Wei (Biofouling, 2014)

Regulation and function of Arabidopsis AtGALK2 gene in abscisic acid response signaling - Qiong Zhao; Dashi Yu; Hongping Chang; Xinhong Guo; Congying Yuan; Shuai Hu; Cheng Zhang; Ping Wang; Yu Wang (Molecular Biology Reports, 2013)